In Defense of Safe Spaces: A Phenomenological Account - Fast, Jina (Atlantis, 2018)
The notion of “safe space” is one example of a theoretical and pedagogical resource grounded in studies of marginalized experiences that has recently undergone backlash in dominant culture and the academy. In this essay, I offer a defense of safe spaces using the theoretical resources of phenomenology and offer suggestions for moving past the dichotomy of safe versus unsafe space. I argue that safe space should be understood not as static and acontextual, as truly “safe” or “unsafe,” but through the relational work of cultivating such spaces. Furthermore, far from restricting dialogue in the classroom, safe spaces encourage dialogue through requiring students to utilize critical thinking in their exchanges and through supporting marginalized students whose positions and humanity often fail to be recognized in dominant spaces.